We're No' Awa' Tae Bide Awa': Scotland's Returning Diaspora. Issue 4 (November 2021) - Leith, Murray Stewart; Sim, Duncan
Abstract : At a time when the world is becoming more mobile, and migration levels are high, relatively limited attention has been paid to return migrants. Yet returners can play an important role in their homeland. In Scotland, with a sluggish population growth fuelled entirely by immigration, return movement is an important way of growing the population and the economy. This paper reports on a study of return migrants to Scotland in 2019/20 and discusses their reasons for return, their experiences and their long-term commitment to the country. Respondents generally felt positively about their return and there was considerable support for Scottish independence, particularly if that led to rejoining the European Union. Brexit was an important factor in making Scots feel unwelcome in England and helping to encourage return to Scotland.